PERLINDUNGAN HUKUM PEKERJA KONTRAK BERDASARKAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR: 7/PUU-XII/2014 - Rachmat Ihya' (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2022)
In human life, there are needs of life that cannot be avoided, which is to fulfill no other event except trying, either by entrepreneurship or by working with the status of a worker (laborer). Workers want a harmonious, comfortable work environment and meet a sense of justice without discrimination with the fulfillment of their rights, including the welfare of workers, but employers have a mindset of creating efficiency in all fields including the costs that must be incurred by employers. From this arose various per,origins between employers and workers, especially contract workers. This research uses normative methods with a normative juridical approach, a statutory approach as the main legal material and other materials related to research research results In accordance with the provisions of the Manpower Law that the term worker / contract laborer or Certain Time Work Agreement (PKWT) or Certain Time Work Agreement (PKWT) outsorcing, when working and bound by an employment agreement with employers are all entitled to legal protection that equal, at least equivalent to the rights of protection of workers Of Indefinite Time Work Agreement (PKWTT), both protection of working time, protection of overtime work, protection of rest and leave time, protection of work agreements, protection of wages, protection of decent living needs, protection of minimum wages, protection of holiday allowances, and protection of welfare stipulated through work regulations and collective labor agreements (PKB).